Keratin‐positive fibrotic extraskeletal myxoid chondrosarcoma: a close mimic of myoepithelial tumour. Issue 6 (27th February 2023) - Sugino, Hirokazu; Iwata, Shintaro; Satomi, Kaishi; Mori, Taisuke; Nobusawa, Sumihito; Nagashima, Toshiteru; Matsushita, Yuko; Yatabe, Yasushi; Ichimura, Koichi; Kawai, Akira; Yoshida, Akihiko
Abstract : Aims: Extraskeletal myxoid chondrosarcoma (EMC) is a rare form of adult sarcoma with distinct histology and NR4A3 gene fusion. Immunohistochemically, EMCs are variably positive for S100 protein and neuroendocrine markers. Unlike histologically similar soft‐tissue myoepithelial tumours, keratin expression is rare. Prompted by two recent EMC cases with diffuse keratin expression, we investigated the expression of epithelial markers in a molecularly confirmed cohort of EMC and identified two additional similar cases. Methods and results: Four keratin‐positive EMCs occurred in one man and three women aged 46–59 years. All tumours displayed nonclassic histology with prominent stromal fibrosis, and keratin AE1/AE3 was expressed either diffusely ( N  = 2) or focally ( N  = 2). In one tumour, keratin expression was limited to the sclerotic area. All tumours coexpressed epithelial membrane antigen and two additionally expressed S100 protein or glial fibrillary acidic protein. All tumours harboured NR4A3 fusions, including TAF15::NR4A3 ( N  = 1) and EWSR1::NR4A3 ( N  = 3). Two cases were initially considered as most consistent with myoepithelial tumours based on widespread stromal fibrosis and keratin expression. DNA methylation analysis classified two tumours tested as EMCs. Conclusions: We identified a small subset of EMCs characterised by keratin expression and prominent stromal fibrosis. This histological pattern must be recognised in the differential diagnosis of myoepithelial tumours because misclassification may lead to the erroneous prediction of tumour behaviour and may alter patient management. NR4A3 genetic analysis should be considered even in the face of keratin expression and prominent stromal fibrosis. Abstract : This study identified a small subset of extraskeletal myxoid chondrosarcoma characterised by keratin expression and prominent stromal fibrosis. This histological pattern must be recognised in the differential diagnosis of myoepithelial tumours because misclassification may lead to the erroneous prediction of tumour behaviour and may alter patient management.